2022
DOI: 10.1111/mcn.13430
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term effects of fresh mother's own milk in very preterm infants

Abstract: Fresh mother's own milk (MOM) can protect preterm infants from many complications. Often MOM is pasteurized for safety, which can deactivate cellular and bioactive components with protective benefits. Questions remain regarding whether pasteurized MOM provides the same benefits as fresh MOM. The aim of this study was to evaluate the association and feasibility of feeding very preterm infants with fresh MOM. This prospective cohort study included 157 very preterm infants born before 32 weeks' gestational age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Our study shows that feeding with MOM in the first 2 weeks of life significantly reduces the risk of BPD, which is in line with the findings of Huang et al (54) and Patel et al (55) , who reported a 9·5 % reduction in the probability of BPD for each 10 % increase in the volume of breast milk consumed. Another meta-analysis and retrospective study also found that breast-feeding was associated with a lower risk of BPD (56) .…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that feeding with MOM in the first 2 weeks of life significantly reduces the risk of BPD, which is in line with the findings of Huang et al (54) and Patel et al (55) , who reported a 9·5 % reduction in the probability of BPD for each 10 % increase in the volume of breast milk consumed. Another meta-analysis and retrospective study also found that breast-feeding was associated with a lower risk of BPD (56) .…”
Section: Discussionsupporting
confidence: 93%
“…Adverse events related to colostrum feeding, including intestinal infection caused by colostrum contamination ( 21 , 22 ), feeding errors, or omissions, were collected and recorded by NICU nurses. Nosocomial intestinal infections could be due to bacterial infection in the gastrointestinal tract after ingesting contaminated colostrum due to improper colostrum collection or transportation or improper disinfection of breast pump accessories and collection cups.…”
Section: Study Methodsmentioning
confidence: 99%
“…A decrease in common reasons for preterm infant morbidity was found in three studies (Dicky et al, 2017;Huang et al, 2023;Sun et al, 2019). A significant decrease in BPD (OR = 0.40, 95% CI [0.27, 0.67], p < 0.001) was found by Dickey et al ( 2017), who compared NICUs with a feeding policy that supported the use of rMOM versus those with policies requiring pasteurization of MOM for infants < 1500 g. In a prospective cohort study (N = 157), Huang et al (2023) also found an improvement in BPD for preterm infants fed rMOM (OR = 0.345, 95% CI [0.15, 0.77], p = 0.010).…”
Section: Non-nutritional Growth and Developmentmentioning
confidence: 95%
“…One study was appraised as moderate owing to the risk of sampling bias (de Oliveira et al, 2017). The remaining six studies were appraised as strong (Cossey et al, 2013(Cossey et al, , 2014de Halleux et al, 2019;Dicky et al, 2017;Huang et al, 2023;Sun et al, 2019). A summary of included study variables, measurement processes, key findings, and quality is provided in Table 2.…”
Section: Quality Analysismentioning
confidence: 99%
See 1 more Smart Citation